Penentuan Permeabilitas Magnet Melalui Percobaan Induksi Magnet dengan Logger Lite - Sri Mugi Lestari; Yusro Al Hakim; Siska Desy Fatmaryanti (Universitas Muhammadiyah Purworejo, 2018)
In magnet world learning, the discussion of the µ magnetic permeability concept has not yet been addressed specifically. The magnetic permeability often discussed is the µ0 vacuum permeability whose value is 4p x 10-7 Tm/A. In fact, the permeability value of objects is not the same as the vacuum permeability. Therefore, it is necessary to conduct experiments on this in order to obtain an adequate understanding of its concepts. The experimental devices include Logger Lite devices, solenoids, computer, power supply, and two types of ferromagnetic materials i.e. steel and white metal which are precisely similar in both lengths. The deciding of the material permeability is done by placing the materials on the solenoid varying electric current (i) which flows in the solenoid and records the induction field produced (B). Then, based on the data set of I towards B, it’s done a linear regression. The material permeability is determined from the slope of the graph.Based on the experiment, the permeability value of vacuum results mo = (4p ± 0,34) x 10-7 Tm/A. Whereas, for each experimented material it shows that the steel is is m = (8.24 ± 0,008) x 10-6 Tm/A and the white metal is m = (1.85 ± 0,002) x 10-5 Tm/A. Based on the experiment, it’s obvious that the permeability concept seems more and more tangible.